DIDACTIC-METHODICAL BASIS OF TRAINING IN LANGUAGE READING - Космуратов, Алтынбек; Тукмирзаева , Айгерим (Журнал иностранных языков и лингвистики, 2025)
Familiarising oneself with the culture of the country of the target language has been one of the main tasks since antiquity. Teaching of classical languages, as well as interpretation of religious texts, is not conceivable without cultural commentary. The temporary state educational standard among the goals of teaching a foreign language at the basic level includes education of pupils "positive attitude to a foreign language, culture of the people speaking this language. Education by means of a foreign language presupposes... knowledge of culture, history, realities and traditions of the country of the learnt language.